Wie verbreitet sind Depression, Angst und Selbstmordgedanken unter Migranten in Deutschland? (PPmP - Psychotherapie · Psychosomatik · Medizinische Psychologie, 2017)
Depression, anxiety and suicidal ideation among 1st and 2nd generation migrants - results from the Gutenberg health study. Beutel ME, Jünger C, Klein EM et al. BMC Psychiatry 2016; 16: 288. Doi: 10.1186/s12888-016-0995-2